Vocational careers of retired Olympic athletes from Switzerland: A person-oriented study - Schmid, M. J.; Örencik, M.; Schmid, J.; Nagel, S.; Conzelmann, A. (International Review for the Sociology of Sport, 2022)
For many high-performance athletes, competing in the Olympic Games is a major goal. Achieving this goal requires more than ever substantial investments of time and personal resources towards the sports career over several years. Thus, some athletes neglect other areas of life (e.g. education), which can pose a problem for the time after high-performance sport, while other athletes pursue a dual career. Previous studies have shown that former high-performance athletes achieved higher levels of education and better vocational positions than the general population. Due to the advancing professionalization and commercialization of high-performance sport, the question emerges whether these results are valid for athletes that are more recently retired. In addition, cross-cultural generalisability of these findings are of interest. For this purpose, 341 former athletes representing Switzerland at the Olympics were surveyed about their athletic, educational, and vocational careers. It turns out that these athletes obtained more degrees of higher education than the general population. Relative to their siblings, they have higher school-leaving certificates and work in more prestigious occupations. Following the holistic-interactionistic paradigm, person-oriented analyses was performed and revealed nine - mostly satisfactory - vocational career patterns. Hence, involvement in high-performance sport facilitates rather than hinders a successful vocational career.